Viscosity and Flow Properties of Cooked Milled Rice Slurries - Siscar-Lee, J. J. H.; Juliano, Bienvenido O.; Baños, Los; Tsuji, S.; Chikubu, S.; Faure, J. (Wiley, 1991)
The applicability of a microcone plate viscometer for measuring some rheological properties of cooked milled rice slurries was studied on milled rices differing in cooked rice texture properties. Viscosity and flow parameters of 10 or 12.5% boiled milled rice slurries were estimated by Power Law Model with a Wells‐Brookfield RVTCP microcone plate viscometer with 2.4 cm diam. 1.565° cone at 25°C and compared with data from other methods. Cooking of the sample was critical in obtaining reproducible results. Selected pairs of samples of similar amylose contents differing in cooked‐rice texture properties by sensory and instrument methods differed also in Power Law parameters flow behavior index n and consistency coefficient m. Apparent viscosity at 10 and 20 rpm may be used to index m, but not n. Differences in m and apparent viscosity were not always those predicted by other texture indexes. Alkali spreading value at adjusted KOH concentrations may be useful in texture differentiation among rices with similar values in 1:7% KOH.